Natural Product Nitric Oxide Chemistry: New Activity of Old Medicines - Jiang, Hong (Hindawi Publishing Corporation, 2012)
The use of complementary and alternative medicine (CAM) as a therapy and preventative care measure for cardiovascular diseases (CVD) may prove to be beneficial when used in conjunction with or in place of conventional medicine. However, the lack of understanding of a mechanism of action of many CAMs limits their use and acceptance in western medicine. We have recently recognized and characterized specific nitric oxide (NO) activity of select alternative and herbal medicines that may account for many of their reported health benefits. The ability of certain CAM to restore NO homeostasis both through enhancing endothelial production of NO and by providing a system for reducing nitrate and nitrite to NO as a compensatory pathway for repleting NO bioavailability may prove to be a safe and cost-effective strategy for combating CVD. We will review the current state of science behind NO activity of herbal medicines and their effects on CVD.